PCNA EXPRESSION IN CAGA STRAIN H. PYLORI GASTRITIS: IMMUNOHISTOCHEMICAL AND INSITU HYBRIDIZATION STUDY (Iraqi Journal of Medical Sciences, 2016)
Background:Carriage of Helicobacter Pylori (H. Pylori) in the human stomach is associated with increased risk of peptic ulcer disease, distal gastric adenocarcinoma and gastric B-cell mucosa associated lymphoid tissue lymphoma. Several studies have shown increased evidence of increased cell proliferation in the gastric mucosa both in human carrying H. Pylori, and animal model of H. Pylori infection.Objective:To study the immunohistochemical expression of Proliferating cell nuclear antigen (PCNA), as a proliferative marker in the gastric mucosa of patients infected with CagA Helicobacter Pylori demonstrated by insitu hybridization method.Methods:Gastric antrum and corpus biopsies from 99 patients with dyspeptic symptoms (50 men, 49 women, and median age 40) were analyzed for H. pylori, presence of chronic inflammation, intestinal metaplasia, and atrophy according to updated Sydney system. Insitu hybridization technique was done to detect cagA H. pylori. Immunostaining for PCNA (Avidin- Biotin method) was performed on paraffin embedded tissue specimens.Results:Forty four patients (44.44%) had H. Pylori cagA positive strain. Atrophy of gastric mucosa was present in 14 (14.14 %) patients. Intestinal metaplasia was present in 8 (8.08%) patients. The frequency of atrophy was significantly higher in cagA H. Pylori gastritis than non-cagA H. Pylori gastritis (p=0.041). The frequency of intestinal metaplasia was significantly higher in cagA H. Pylori gastritis than non-cagA H. Pylori gastritis (p=0.023). PCNA labeling index (LI) of the gastric glands was significantly higher in presence of atrophic alterations (p
Keywords: cag A H pylori gastritis; PCNA immunohistochemical expression